Development of students’ academic literacies viewed through a political ethics of care lens - Dison, A. (South African Journal of Higher Education, 2018)
This article explores insights which the political ethics of care (Tronto 1993; 2013) offers to academic literacies development of students. Research on ethics of care has been conducted in contexts ranging from micro to macro levels. However there has been no research on academic literacies development using this lens. In this article, data on academic literacy development within a health sciences faculty at a South African university is re-analysed through an ethics of care lens. Curriculum and programme alignment, departmental relationships and ethos and institutional approach to academic literacies development are considered through this lens. While the initial research project focused on student acquisition of dominant academic literacies, this article explores the insights that care ethics can bring to a “transformative” approach to academic literacies (Lillis and Scott 2007) and argues that care ethics can make a contribution to the decolonisation of education.